Individual and Simultaneous Stripping Voltammetric and Mutual Interference Analysis of Cd2+, Pb2+ and Hg2+ with Reduced Graphene Oxide-Fe3O4 Nanocomposites. (10th December 2015) - Xiong, Shiquan; Yang, Bingyi; Cai, Dongqing; Qiu, Guannan; Wu, Zhengyan
Abstract: This study attempts to understand the stripping behaviors and mutual impact of different metal ions in electrochemical detection. A reduced graphene oxide-Fe3 O4 (rGO-Fe3 O4 ) nanocomposites with small-sized Fe3 O4 is prepared by a simple and one-pot synthesis method. The morphology and structure of the nanocomposites are investigated by scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transform infrared spectrometer and X-ray diffraction. The electrochemical behaviors of nanocomposite electrode are characterized by cyclic voltammetry and electrochemical impedance spectroscopy. The individual and simultaneous stripping analysis of Cd 2+, Pb 2+ and Hg 2+ using rGO-Fe3 O4 electrode are performed by square wave anodic stripping voltammetry (SWASV) under optimized condition, and experimental data show that there are differences in some parameters such as sensitivities and detection limits, etc. To further understand phenomena, a series of interference tests are systematically evaluated by SWASV in detail. The experimental results demonstrate that determination of Cd 2+ is easy to be influenced by Pb 2+ and Hg 2+ . At last, the proposed electrode is used to analyze content of Pb 2+ in soil sample. The result obtained at the nanocomposite electrode is comparable to that obtained by inductively coupled plasma atomic emission spectroscopy, indicating a good accuracy. The sensor could provide an effective detection and analysis method for heavy metal ions.